Effect of α-Glucosylation on the Stability, Antioxidant Properties, Toxicity, and Neuroprotective Activity of (–)-Epigallocatechin Gallate - Gonzalez-Alfonso, Jose L.; Peñalver, Pablo; Ballesteros, Antonio O.; Morales, Juan C.; Plou, Francisco J. (Frontiers in Nutrition, 2019)
(‒)-Epigallocatechin gallate (EGCG), the predominant catechin (≥ 50%) in green tea (Camellia sinensis), displays several bioactive properties but its stability and bioavailability are low. In this work, the properties of two α-glucosyl derivatives of EGCG (3’- and 7-O-α-D-glucopyranoside), obtained by enzymatic synthesis, were assessed. The α-glucosylation enhanced the pH and thermal stability of EGCG. The analysis of scavenging activity towards ABTS˙+ radicals showed that the α-glucosylation at C-7 of A-ring caused a higher loss of antioxidant capacity compared with the sugar conjugation at C-3’ of B-ring. The 3’-glucoside also showed higher potential to alleviate intracellular ROS levels and to boost REDOX activity. The toxicity of EGCG and its monoglucosides was tested in human SH-S5Y5 neurons, RAW 264.7 macrophages, MRC5 fibroblasts and HT-29 colon cancer cells. Interestingly, the 3’-O-α-D-glucoside increased the viability of neural cells in vitro (2.75-fold at 100 µM) in the presence of H2O2, whilst EGCG gave rise only to a 1.7-fold enhancement. In conclusion, the α-glucoside of EGCG at C-3’ has a great potential for nutraceutical, cosmetic and biomedical applications.